2015
DOI: 10.4238/2015.june.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the obp5 gene in Apis mellifera ligustica and Apis cerana cerana

Abstract: ABSTRACT. Apis mellifera ligustica and A. cerana cerana exhibit differences in olfactory sensitivity to odors from nectariferous plants and diseased broods. It is presumed that the differences in odorant-binding proteins (OBPs) between these 2 species contribute to their olfactory sensitivity. We compared the sequences, temporal expression pattern, and binding properties of the 2 OBP-encoding genes. We cloned the Amobp5 and Acobp5 genes. Among the ligands tested, phenethyl acetate was the most variable, with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A. cerana cerana is the major honeybee species in China and plays an important role in ecological balance and the agricultural industry. A. cerana cerana has the advantages of a long period of collecting honey, low food cost and good resistance to disease [24,25]. However, in recent years, the survival of A. cerana cerana has been seriously threatened due to various environmental stresses including the indiscriminate use of pesticides, infectious diseases, and global warming [26].…”
Section: Introductionmentioning
confidence: 99%
“…A. cerana cerana is the major honeybee species in China and plays an important role in ecological balance and the agricultural industry. A. cerana cerana has the advantages of a long period of collecting honey, low food cost and good resistance to disease [24,25]. However, in recent years, the survival of A. cerana cerana has been seriously threatened due to various environmental stresses including the indiscriminate use of pesticides, infectious diseases, and global warming [26].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the affinity and selectivity of the OBP2 protein in plant odors has been demonstrated, showing its physiological role in the recognition of forage species, especially in those that present compounds such as 1-8 cineole in their aroma [58]. Additionally, Zhao et al [59] reported the crucial role of the OBP5 protein in the larval care processes within the hive. This protein has an affinity for volatile compounds released by larvae when they are affected by different pathogens, suggesting that the recognition of these volatile compounds by nurse bees could aid in recognizing diseased larvae and caring for health larvae, being key in the sanitary maintenance of the brood within the hive.…”
Section: Discussionmentioning
confidence: 98%
“…Such hygienic behavior can accordingly enable bee colonies to resist a range of potentially devastating diseases such as European foulbrood and chalkbrood disease [8][9][10]. In this regard, Eastern honeybees (Apis cerana) are considered to be somewhat better adapted than Western honeybees (Apis mellifera), in that they carry fewer pathogens and parasites [11][12][13][14][15][16][17] and produce a more diverse array of antimicrobial peptides when attacked or irritated by pathogens, thereby minimizing damage [18]. Compared with A. mellifera, A. cerana bees are thus considered to be more resistant to pathogens and more e cient with respect to their hygienic behavior, in terms of both uncapping and removal [19,20].…”
Section: Introductionmentioning
confidence: 99%